Inhibition of RFX6 Suppresses the Invasive Ability of Tumor Cells Through the Notch Pathway and Affects Tumor Immunity in Hepatocellular Carcinoma - Song, Mu; Kuerban, Mulati; Zhao, Lu; Peng, Xiaolin; Xu, Youqin (Frontiers in Oncology, 2021)
Background: DNA-binding protein RFX6 was overexpressed in hepatocellular carcinoma and its expression level was correlated with the prognosis and immune cell infiltration in liver hepatocellular carcinoma. However, the mechanism of abnormal expression and biological effects of RFX6 in liver cancer remains unknown. Methods: To understand the specific expressing mechanism of RFX6 in liver cancer, we performed bioinformatic prediction, CHIP-qPCR assay, Co-IP and dual-luciferase assay to assess the regulating mechanism of RFX6. In the meantime, a series of biological experiments in vivo and vitro were conducted to analyze the biological significance of RFX6 in hepatocellular carcinoma. Results: We demonstrated that the knockdown of RFX6 in liver cancer cells significantly suppressed the proliferation, migration and invasion of cancer cells. Moreover, inhibition of RFX6 could stimulate immune response of T cells. Among lots of interacting proteins, we revealed RFX6 directly binding to DTX2, regulator of Notch signaling pathway by targeting NOTCH1, and help it`s transcription stability. Furthermore, we discovered miRNA-542-3p, expression of which was decreased in hepatocellular carcinoma, was directly involved in negative regulation of the expression of RFX6. Conclusions: In summary, we discovered a miRNA-542-3p-RFX6-DTX2-NOTCH1 regulatory pathway played significant roles in the tumor progression of liver hepatocellular carcinoma.